1980
DOI: 10.1136/thx.35.10.788
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that rifampicin can be used safely for non-tuberculous diseases.

Abstract: The incidence of primary resistance to rifampicin in Mycobacterium tuberculosis has been analysed in countries where rifampicin is restricted to use for treating tuberculosis and in countries where its use is not restricted. There is no evidence that rifampicin-resistant M tuberculosis strains are more common where the use of the drug is unrestricted. Resistance to rifampicin is less common than is resistance to streptomycin or to isoniazid. We can thus see no danger of producing resistant strains of M tubercu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Because elevated rifampicin dosages for filariasis cure are predicted in a 1–2 week dose exposure time frame, this is unlikely to result in resistant strains of M tuberculosis (TB), as there is no evidence for rifampicin resistance occurrence when administered for short periods of time 73 , 74 .…”
Section: Discussionmentioning
confidence: 99%
“…Because elevated rifampicin dosages for filariasis cure are predicted in a 1–2 week dose exposure time frame, this is unlikely to result in resistant strains of M tuberculosis (TB), as there is no evidence for rifampicin resistance occurrence when administered for short periods of time 73 , 74 .…”
Section: Discussionmentioning
confidence: 99%
“…This resistance is known to occur if rifampicin is used as monotherapy or when treating infections with a very high bacterial load [9]. In 1980, Acocella et al reported that the incidence of rifampicinresistant tuberculosis strains was not higher in countries where rifampicin was frequently used in comparison with countries with a restrictive use of rifampicin and therefore concluded that this fear was unjustified [10]. Nowadays, it is a common antibiotic prescribed for foreign body-materialrelated infections, including PJI.…”
Section: Historical Overviewmentioning
confidence: 99%
“…In vitro studies demonstrate that resistance to rifampicin easily develops when used as monotherapy, in particular when the bacterial load is high [44]. This phenomenon is illustrated in a clinical study demonstrating that inadequate surgical debridement and inadequate induction therapy with intravenous antimicrobials resulted in a higher odds of developing rifampicin-resistant strains [10]. However, if a thorough surgical debridement with adequate bacterial load reduction is performed followed by rifampicin combination therapy, the occurrence of rifampicin resistance is probably very unlikely.…”
Section: When To Startmentioning
confidence: 99%
“…First, epidemiological evidence has been adduced [4,5] to show that no more primary resistance is found in strains of M. tuberculosis isolated in countries where RIF is freely available than in countries where it is used only in combined therapy for tuberculosis.…”
Section: Discussionmentioning
confidence: 99%